Organisms in Operative site in an urban hospital of Dhaka city: An urgent need to develop an infection control program in Bangladesh (Bangladesh Journal of Medical Microbiology, 2013)
The study was carried out from July 2008 to June 2009 to evaluate the presence of organisms in operative and post operative room in an urban hospital of Dhaka city. Environmental samples were collected from different sources of surrounding of patient in operative and post operative room. A total of 120 samples were collected from the floor, bed sheets, OT instruments, dressing materials, nasogastric and endotracheal tube, catheters, etc. The most predominant isolated organism was E. coli (40%) followed by S. aureus (24%). Microbial isolates were obtained from the hands of hospital staffs and attendance in the same hospital and the percentage of prevalence of E. coli was more in the hands of attendances (60%) than hospital staffs (40%) ; but the presence of S. aureus and Pseudomonas sp. were less in attendances hands than hospital staffs hands. The other organisms that were present in hands of hospital staffs and attendances were Proteus sp, S.epidermidis, and Klebsiella sp. An effective infection control practices like hand washing and the use of hypochlorite solution, gluteraldehyde and sanitation with 70% ethyl alcohol was found to be very effective in reduction of microbial contaminates in operative and post operative room.DOI: http://dx.doi.org/10.3329/bjmm.v7i1.19317 Bangladesh J Med Microbiol 2013; 07(01): 20-24